3Cat-1 project: a multi-payload CubeSat for scientific experiments and technology demonstrators. Issue 1 (1st January 2017) - Jove-Casurellas, Roger; Araguz, Carles; Via, Pol; Solanellas, Arnau; Amézaga, Adrià; Vidal, David; Muñoz, Joan Francesc; Marí, Marc; Olivé, Roger; Saez, Alberto; Jané, Jaume; Bou-Balust, Elisenda; et al.
ABSTRACT: This article introduces 3 Cat-1, the first project of the Technical University of Catalonia to build and launch a nano-satellite. Its main scope is to develop, construct, assemble, test and launch into a low Earth orbit a CubeSat with seven different payloads (mono-atomic oxygen detector, graphene field-effect transistor, self-powered beacon, Geiger radiation counter, wireless power transfer (WPT), new topology solar cells and WPT experiment), all fitted in a single-unit CubeSat. On one hand, this is mainly an educational project in which the development of some of the subsystems is carried out by undergraduate and postgraduate students. The satellite demonstrates its capabilities as a cost-effective platform to perform small scientific experiments and to demonstrate some of the new technologies that it incorporates.